Ubiquitination of mammalian AP endonuclease (APE1) regulated by the p53-MDM2 signaling pathway - Busso, Carlos S. (2009)
APE1/Ref-1 is an essential DNA repair/gene regulatory protein in mammals of which intracellular level significantly affects cellular sensitivity to genotoxicants. The APE1 functions are altered by phosphorylation and acetylation. We here report that APE1 is also modified by ubiquitination. APE1 ubiquitination occurred specifically at Lys residues near the N-terminus, and was markedly enhanced by MDM2, the major intracellular p53 inhibitor. Moreover, DNA damaging reagents and nutlin-3, an inhibitor of MDM2/p53 interaction, increased APE1 ubiquitination in the presence of p53. Downmodulation of MDM2 increased APE1 level, suggesting that MDM2-mediated ubiquitination can be a signal for APE1 degradation. In addition, unlike the wild-type APE1, ubiquitin-APE1 fusion proteins were predominantly present in the cytoplasm. Therefore, monoubiquitination not only is a prerequisite for degradation, but may also alter the APE1 activities in cells. These results reveal a novel regulation of APE1 through ubiquitination.